REDESIGN JEMBATAN SUNUT KABUPATEN SEMARANG MENGGUNAKAN STRUKTUR PELENGKUNG TIPE A- HALF THROUGH ARCH BRIDGE - Rahmasari, Maria Asysyifa; Praptiningrum, Retno Dwi; Budirahardjo, Slamet; Rizani, Mohammad Debby (Universitas PGRI Semarang, 2024)
The Sunut Bridge is a bridge that crosses the Jragung River which connects Semarang Regency and Demak Regency. The initial planning for the Sunut Bridge used a prestressed concrete structure with a total length of the main bridge of 60 meters. This bridge is divided into 4 parts. From the author's assessment, the use of prestressed concrete structures with many pillars is considered to cause design waste and give the impression of stiffness to the bridge. Apart from that, seeing that the condition of the river during floods often brings flooding, thereby reducing the effective linear waterway of the river, a bridge construction was re-planned with minimal pillars using an arch structure. In this planning, the Sunut Bridge was re-planned to use a steel arch structure type A Half Through Arch Bridge. From the planning results, the vechile floor plat tickness was 23 cm. The longitudinal girder profile used is WF 800x300x16x30 and the cross girder profile WF 900x300x16x28. The next stage of calculating the primary and secondary structures is carried out by calculating the working loads which refer to SNI 1725:2016 and RSNI T-02-2005 regulations to obtain a box prifile for the main structure of the arch bridge.